Three Novel De Novo ZEB2 Variants Identified in Three Unrelated Chinese Patients With Mowat-Wilson Syndrome and A Systematic Review - Fu, Youqing; Xu, Wanfang; Wang, Qingming; Lin, Yangyang; He, Peiqing; Liu, Yanhui; Yuan, Haiming (Frontiers in Genetics, 2022)
Background:ZEB2 gene mutations or deletions cause Mowat-Wilson syndrome (MWS), which is characterized by distinctive facial features, global developmental delay, intellectual disability, epilepsy, friendly and happy personalities, congenital heart disease, Hirschsprung disease and multiple congenital anomalies. Currently, more than 300 MWS patients have been described in the literature, and nearly 280 variants in ZEB2 have been identified. Methods: In this study, we report three unrelated Chinese patients presenting multiple congenital anomalies that were consistent with those of MWS. Whole-exome sequencing (WES) was used to identify the causative variants. Results: WES identified two novel de novo frameshift variants in ZEB2 (NM_014795.4:c.2136delC, p. Lys713Serfs*3 and c.2740delG, p. Gln914Argfs*16) in patients 1 and 2, respectively, and a novel de novo splicing variant in ZEB2 (NM_014795.4:c.808-2delA) in patient 3, all of which were confirmed by Sanger sequencing. Next, we systematically reviewed the clinical characteristics of Chinese and Caucasian MWS patients. We revealed a higher incidence of constipation in Chinese MWS patients compared to that previously reported in Caucasian cohorts, while the incidence of Hirschsprung disease and happy demeanor was lower in Chinese MWS patients and that epilepsy in Chinese MWS patients could be well-controlled compared to that in Caucasian MWS individuals. Conclusion: Our study expanded the mutation spectrum of ZEB2 and enriched our understanding of the clinical characteristics of MWS. Definitive genetic diagnosis is beneficial for the genetic counseling and clinical management of individuals with MWS.